Integrating Federal Statistics on Children: Report of a Workshop - Medicine, National Research Council and Institute of; Education, Division of Behavioral and Social Sciences and; Education, Commission on Behavioral and Social Sciences and; Families, Committee on National Statistics and Board on Children and (National Academies Press, 1995)
Those who make and implement policies for children and families are seriously hampered by several features of the federal statistical system: categorical fragmentation, sampling strategies that follow adults and families rather than children, and lack of longitudinal data on children. This volume examines the adequacy of federal statistics on children and families. It includes papers on the relevant aspects of health care reform, family and community resources, interpersonal violence, the transition to school, and educational attainment and the transition to work.